Association of Admission Platelet Crit with In-Hospital Outcomes in Non ST-Elevation Myocardial Infarction (NSTEMI) - Mushtaq, Huma; Shabbir, Muhammad; Mukarram, Shahid; Altaf , Maria (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the association of admission plateletcrit with in-hospital outcomes in non ST-elevation myocardial infarction (NSTEMI).Study Design: Analytical Cross-sectional studyPlace and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi; from Nov 2023 to Apr 2024Methodology:  Using non-probability consecutive sampling, 270 patients were included in this study. ECG findings were noted. Patients were divided into three tertiles based upon plateletcrit value such as T1=lower than normal PCT value (0.22). PCT values were obtained from complete blood count sent at the time of presentation to AFIC emergency using Mandray BC 6200 CBC analyzer available at the AFIC pathology laboratory.Results: The study included 270 patients, out of which 137(50.7%) were males and 133(49.3%) were females and median age was 62.00(55.00-70.00) years. T1, T2 and T3 had 71(26.3%), 34(12.6%) and 165(61.1%) patients, respectively. Significant frequency differences of hypertensive and hyperlipidemia patients, and in-hospital outcomes were found between tertiles (p